Seismic Risk and Toxic Waste Disposal: A Discussion - Berry, M.; Hasegawa, H. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1979)
Summary Earthquakes, whether natural or induced, pose a significant risk to the disposal of toxic wastes by burial or fluid injection in the crust. Methodology exists for assessing the ambient seismic risk at moderately low levels of probability, but for greater degrees of conservatism the assessment is essentially deterministic. Such estimates are considered appropriate for periods comparable to that of the available seismic history but an improved understanding of the nature of currently active seismic zones is required for the estimates to be applied with confidence to periods of time measured in thousands of years. The potential hazards associated with this natural seismic risk can be mitigated by appropriate engineering design and practice. Induced seismicity associated with mining excavations, thermally induced stresses or fluid injection can be controlled by appropriate engineering design and operational procedure.